2020
DOI: 10.1038/s41467-020-19372-x
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine oxidation and disulfide formation in the ribosomal exit tunnel

Abstract: Understanding the conformational sampling of translation-arrested ribosome nascent chain complexes is key to understand co-translational folding. Up to now, coupling of cysteine oxidation, disulfide bond formation and structure formation in nascent chains has remained elusive. Here, we investigate the eye-lens protein γB-crystallin in the ribosomal exit tunnel. Using mass spectrometry, theoretical simulations, dynamic nuclear polarization-enhanced solid-state nuclear magnetic resonance and cryo-electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…Enhancements of up to 150-fold have been reported on complex systems such as GPCRs (Joedicke et al, 2018) or ribosome nascent chain complexes (Schulte et al, 2020). This significant boost in sensitivity can be highly beneficial for real-time NMR applications.…”
Section: Dnpmentioning
confidence: 99%
“…Enhancements of up to 150-fold have been reported on complex systems such as GPCRs (Joedicke et al, 2018) or ribosome nascent chain complexes (Schulte et al, 2020). This significant boost in sensitivity can be highly beneficial for real-time NMR applications.…”
Section: Dnpmentioning
confidence: 99%
“…Biomacromolecules can be unfolded in many different ways (Fürtig et al, 2007b;Roder et al, 2004). Proteins can be chemically denatured using high concentrations (6-8 M) of guanidinium chloride (GdnCl) (Logan et al, 1994;Zeeb and Balbach, 2004) or urea (Egan et al, 1993;Neri et al, 1992;Schwalbe et al, 1997), but also organic solvents including 2,2,2-triflouroethanol (TFE) or dimethyl sulfoxide (DMSO) (Buck, 1998;Buck et al, 1995Buck et al, , 1993Nishimura et al, 2005). The (re-)folding of chemically denatured proteins can then be initiated with a rapid dilution into native buffer conditions (Balbach et al, 1995) or vice versa for unfolding of native proteins (Kiefhaber et al, 1995).…”
Section: Rapid Mixingmentioning
confidence: 99%
“…In other research addressing the role of disulfides in influencing the conformational dynamics of proteins, it was found that the introduction of single disulfides spanning a large portion of the lysozyme shifted both the structure and dynamics of hydrophobic core residues of the protein [ 127 ]. In a recent landmark study that utilized a combination of biophysical and computational techniques (mass spectrometry, theoretical simulations, dynamic nuclear polarization-enhanced solid-state nuclear magnetic resonance and cryo-electron microscopy), it was demonstrated that thiol groups of cysteines undergo chemical mutation to form S-glutathionylated and S-nitrosylated adducts and impacted the formation non-native disulfide bonds [ 128 ]. This covalent chemical modification was found to occur prior to chain release, supported by arguments that since the ribosome exit tunnel provides sufficient space even for disulfide bond formation, it is not surprising to detect these chemo-mutated variants.…”
Section: Learnings From Oxidative Protein Foldingmentioning
confidence: 99%